Poem of P. A. Oyunsky "Tuyarima Kuo Fair-Faced": A Textological Aspect - Grigorieva, Lyudmila Pavlovna (Journal of History Culture and Art Research, 2018)
This article focuses on "Tuyarima Kuo Fair-faced" poem’s text by Yakut literature classic P. A. Oyunsky (1893-1939) in the aspect of textology and publishing practices. On the basis of comparative analysis of manuscript text and the lifetime edition of 1930 it is established that the text of this edition is the closest to the manuscript, it fully expresses the author’s will: there are practically no discrepancies, the author’s punctuation is preserved. In this regard, it is concluded that this text can be recognized as the main text of the poem. The study of the manuscript also allowed to reveal new facts reflecting the creative work of P.A. Oyunsky on his text: changing the name of the poem’s heroes. Conducted comparative analysis of manuscripts and lifetime edition of 1930 with the 1959th, 1992nd publication showed a significant difference in punctuation, spelling, cases, division into sentences, the deletion of the paragraph, the transfer of sentences, discrepancies in the spelling of character, etc. Hence, first of all, the author’s marks in the text of the poem should be restored, because they express the individual style of the writer, also the missing commas in the manuscript and the first edition must be put according to the rules of modern punctuation, which is done in the publication in 1992nd; second of all, the spelling of the writer must be fully restored according to the text of the publication in 1930. In general, the results allow to raise the question of the need for special research in the aspect of textological and publishing practices of all texts of Oyunsky’s works with the aim of publishing critically established texts, which would reflect the last will of the writer.